Elastic and Ultrasonic Properties of XBi (X: B, Cm and U) - Kaushik, Shivani; Singh, Devraj; Mishra, Giridhar (Asian Journal of Chemistry, 2012)
The elastic and ultrasonic properties of boron, uranium and curium monobismuthides are reviewed in this article. We present computation of ultrasonic Grüneisen parameters <100>, <110> and <111> directions in the temperature range 100 to 300 K using second and third order elastic constants. The second and third order elastic constants are also calculated using Coulomb and Born-Mayer potential upto second nearest neighbour. The mechanical properties of BBi are better than UBi and CmBi due to its high valued elastic constants. The chosen materials are stable as they satisfied Cauchy's stability criteria. The ultrasonic Grüneisen parameters for CmBi are found highest. Hence CmBi is more sensitive to temperature. Obtained results are discussed with available experimental/theoretical results.